160 Preliminary results of a case-control study of night shift work and breast cancer among Hong Kong women. (11th October 2013) - Tse; Wang; Chan; Kwok; Leung; Yu
Abstract : Objectives: Breast cancer is the leading cause of cancer morbidity and mortality among women in Hong Kong, and the rate is accelerating. Meanwhile, the prevalence of night shift work in Hong Kong women is also increasing. We aim to present the preliminary results of an ongoing case-control study of breast cancer among Hong Kong women in the EPICOH 2.0.13. Methods: We are consecutively recruiting all newly diagnosed breast cancer cases and age-matched controls from several hospitals and we expect to collect 1, 066 cases and 1, 066 controls by the end of 2013. A standardised questionnaire was used to collect information on each participant's lifetime exposure to night shift work, exposure to light at night, sleep disorders, environmental exposures to pesticides and other EDCs, occupational exposures, reproductive and anthropometric factors, smoking, diet, alcohol drinking, family cancer history, etc. Results: We have obtained 350 breast cancer cases and 350 controls with a response rate of 92%. The age distribution at the diagnosis of breast cancer (55.1 ± 11.9 vs. 54.2 ± 14.6, p = 0.39) and the menopause status (61.9% vs. 61.0%, p = 0.84) for the cases and controls are comparable. A slightly more controls (92.2%) than the cases (89.9%) are the never smokers. Around 80% cases have records of estrogen receptor (ER) status and 73.3% of them are ER positive, while 52% are positive in progesterone receptor. The proportion of ever exposure of night shift work tends to be low (10%) and this proportion is not significantly higher in cases. Conclusions: This study showed preliminary results regarding the basic characteristics of an ongoing case-control study of breast cancer in Hong Kong women. In addition to patient interview, we have also collected blood samples. We shall be able to present more valuable data in the upcoming EPICOH. Acknowledgement: Research Grants Council, Hong Kong (Project no. 474811).